The Guts of a Torts Class - Austin, Graeme W (Victoria University of Wellington Law Review, 2015)
As a tribute to Professor Bill Atkin's unswerving dedication to the teaching of the law of torts, this article makes a few personal observations about tort law teaching at Victoria University of Wellington. The article's focus is the craft of so-called Socratic teaching, which, broadly described, involves inviting students to participate in classroom dialogue that scrutinises the quality of judicial reasoning. The article links that endeavour to the Law School’s obligation to act as a conscience and critic of society, and to its commitment to inculcate values associated with the rule of law.